Industrial training report: Celestica Malaysia Sdn Bhd / Nurin Sabiha Suhaimi - Suhaimi, Nurin Sabiha (Universiti Teknologi MARA, Perlis, 2023)
This report describes and explains my journey of industrial training at Celestica Malaysia Sdn Bhd within 24 weeks to fulfil the requirement for internship (MGT666). Celestica Malaysia Sdn. Bhd. provides business design services. The Company offers a wide range of services such as logistics, fulfilment, product data management, engineering, and supply chain services for enterprise, communications, consumer, aerospace and defence, industrial, alternative energy, and healthcare sectors. The company was in Kulim, Kedah but I was required to work from home. This report addresses all of the requirements specified by the faculty for the industrial training report. It was divided into three sections: SWOT Analysis, the matching stage, and PESTEL. During that time, I was able to identify and explain the company's strengths, weaknesses, opportunities, and threats. It allows me to concentrate on internal and external factors that may have an impact on the company. Furthermore, industrial training allows me to improve and expand my skills, abilities, and knowledge. It was a good experience and memory because I gained not only experience but also new friends and knowledge. Even though I was working from home, I learned a lot about the working environment and the nature of work, even though it was very different from what I had learned at university.